Homoseksual Dalam Perspektif Hukum Islam - Ramlan Rangkuti Yusuf Rangkuti (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Islamic jurisprudence see that sexual desire is a human base, a natural power that is in a human. So, islamic jurisprudence regulate a human biological sexual desire channel by a marriage, and they don't agree a sexual deviation, such as homosexual. Homosexual is a bad behaviour that is prohibited in islamic jurisprudence based on al-Quran and hadis. Scribes of islamic jurisprudence agree to forbid homosexual, although there are so many opinion about law sanction for them. Some of the scribes say that they have to be killed, have to be punished, such as a judgement for they commit an adultery, and even they say that homosexual will be punished in jail (ta'zir).